Knowledge, attitude and perceived barriers to telemedicine among medical professionals: a cross sectional study - Jossy, Preeti Elizabeth; Nandini, Parvathi; Nair, Parvathy R.; S., Nimisha J.; S., Niveditha V.; Rahul, Arya (International Journal Of Community Medicine And Public Health, 2024)
Background: Telemedicine, an evolving technology in India's healthcare sector, offers promising avenues for improving healthcare accessibility and delivery. Its successful implementation relies on several factors, including the comprehension of its concepts, skill acquisition, attitude toward technology, and conducive work environments among healthcare professionals. Despite the pressing need for enhanced healthcare in developing countries like India, telemedicine remains more advanced in developed nations. The objective of this study was to evaluate the knowledge, attitude, and perceived barriers to telemedicine among medical professionals at government medical college Trivandrum and KIMS health Trivandrum. Methods: A cross-sectional survey involving 150 medical professionals across various departments was conducted using a structured questionnaire via the Kobo toolbox, an online survey tool. The collected data were analyzed to assess the understanding of telemedicine, attitudes toward its adoption, and barriers encountered by respondents. Results: The analysis revealed that while a commendable 35.3% of respondents exhibited a good understanding of telemedicine, the majority 64.7% lacked sufficient knowledge in this domain. However, there was a positive disposition towards telemedicine adoption, with 64.7% displaying strong positive attitudes, 24.7% expressing moderate attitudes, and 10.7% indicating lower inclinations. Notably, human resource availability emerged as the most prevalent barrier, while sustainable practices were cited least frequently. Conclusions: While many medical professionals showed support for telemedicine, their knowledge was limited, and the study identified multiple barriers to its adoption. Urgent action is needed to narrow the disparity between telemedicine's potential and its actual use in India's healthcare system.